PENDATAAN PENERIMA ZAKAT KANTOR BAZNAS KABUPATEN PROBOLINGGO BERBASIS ANDROID GIS - Muslim Alamsyah; Mochammad Firman Arif (Joutica, 2019)
Zakat is a number of assets that must be issued by Muslims to be given to groups who have the right to receive, such as the poor and the like, according to those stipulated by sharia. The law of zakat is obligatory for every Muslim who has fulfilled certain conditions. The National Zakat Amil Agency (BAZNAS) is the official body and the only one formed by the government based on RI Presidential Decree No. 8 of 2001 which has duties and functions to collect and distribute zakat, infaq, and alms. The purpose of making this research is to build an android application for GIS zakat assistance map (BAZNAS) in probolinggo district. This study uses data collection methods used in this study through observation, which is collecting data obtained from existing documents or stored records, both in the form of transcript notes, books, newspapers, plunging directly to the location to take pictures, and so on. Output targets of this study are in the form of an application for collecting data on zakat assistance from an Android-based Baznas office and will be published in non-accredited national journals. The application can be used by someone who wants to send donations via Smartphone easily. As well as the results of this application, it can map the locations of recipients of Zakat and Donors according to the coordinates of points of different colors. With the application, it can help channeling Zakat in Probolinggo district. Keywords: Zakat, Baznas, Android, GIS